TERRESTRIAL ORGANIC MATTER IN SURFACE SEDIMENTS OF THE BALTIC SEA, NORTHWEST EUROPE, AS DETERMINED BY CUO OXIDATION - Miltner A.; Emeis K.C. (My University, 2001)
We studied the distribution and composition of terrestrial organic matter in sediments of the Baltic Sea (Northwest Europe). To this end, surface sediments from all basins of the Baltic Sea were analyzed for their lignin oxidation product yields and compositions after CuO oxidation. Lignin oxidation product yields depend on the concentration of organic carbon and range from 0.4 to 10.2 mg g-1 total organic carbon (TOC). On the basis of an average of 13 mg g-1 TOC in two river sediments, we estimate that the upper limit of terrestrial organic matter in Baltic Sea sediments is 30% of TOC. The contribution of terrestrial organic matter differed between the individual basins, depending on the distance from runoff discharge areas and on the area occupied by each submarine catchment. Lignin composition showed a relative decrease of angiosperm tissue from the Southwest to the Northeast, reflecting the shift from temperate to boreal vegetation type. The Gotland and the Bornholm Seas, which have no significant river input, were characterized by high relative contributions of nonwoody, strongly altered material. The source may either be a mixture of pollen and peat being eroded from geologically older strata at the seafloor or laterally advected material from the other basins. However, the pronounced compositional differences between the basins indicated that interbasin transport of terrestrial organic matter is less important than direct river input, although river signals can only be traced at a few places in the Baltic Sea.